2015
DOI: 10.2214/ajr.14.14221
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient Values of the Benign Central Zone of the Prostate: Comparison With Low- and High-Grade Prostate Cancer

Abstract: Objective The apparent diffusion Coefficient (ADC) values for benign central zone (CZ) of the prostate were compared with ADC values of benign periphral zone (PZ), benign transition zone (TZ), and prostate cancer, using histopathologic findings from radical prostatectomy as the reference standard. Materials and Methods The study included 27 patients with prostate cancer (mean [± SD] age, 60.0 ± 7.6 years) who had 3-T endorectal coil MRI of the prostate performed before undergoing prostatectomy with whole-mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…To our knowledge, this is the first study of biopsy‐naïve patients reporting the details and the differences of PCa detection and cancer grade in TB by the location of the lesions. Several studies showed the relationship between the location of PCa and MRI findings . Syed et al .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study of biopsy‐naïve patients reporting the details and the differences of PCa detection and cancer grade in TB by the location of the lesions. Several studies showed the relationship between the location of PCa and MRI findings . Syed et al .…”
Section: Discussionmentioning
confidence: 99%
“…All quantitative imaging data were prospectively collected as follows: For determination of lesion apparent diffusion coefficient (ADC), an ROI was drawn on a single axial slice on the ADC map on which the tumor appeared the largest and most conspicuous [10]. The ROI encompassed the entirety of the lesion on the chosen slice.…”
Section: Methodsmentioning
confidence: 99%
“…ADC reflects the mobility of water molecules within tissue, which provides useful contrast in cancerous tumours, where ADC values are generally observed to be lower than healthy tissue. However, the ADC values in PCa and benign tissue overlap substantially, confounding the overall specificity . ADC is a gross measurement that conflates various physiological parameters, including cell size, shape, permeability, subcellular architecture and vascular perfusion effects .…”
Section: Introductionmentioning
confidence: 99%